PELATIHAN DIGITALISASI AKUNTANSI BERBASIS SOFTWARE DENGAN TOPIK PENJUALAN DI SMA SANTO KRISTOFORUS I JAKARTA BARAT - Widjaja, Chelsya; Patricia, Virginia; Ratna Sari, Vinnetta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
PKM software-based accounting digitization training with the topic of sales at SMA Santo Kristoforus I West Jakarta aims to provide an understanding of software-based accounting digitization, the operation of accounting software for sales transactions in trading companies, and financial reporting, especially profit and loss reports for trading companies with the help of accounting software. The problem faced by partners is that there is no software-based digital accounting training at Santo Kristoforus I High School before, so the PKM team is trying to provide a solution by holding software-based accounting digitalization training. The method used in PKM is a training method using theoretical discussions and calculation questions related to sales accompanied by inputting transactions into accounting software. The training at Santo Kristoforus I High School, West Jakarta was carried out on October 27 2023 and November 8 2023, from 14.45 – 16.45, located in the computer laboratory room of Santo Kristoforus I High School. The results of the training contributed positively to the students of Kristoforus High School, where the students /i gain knowledge about software-based digital accounting.